The Safety and Efficacy of the Continuous Peripheral Nerve Block in Postoperative Analgesia of Pediatric Patients - Simić, Dušica; Stević, Marija; Stanković, Zorana; Simić, Irena; Dučić, Siniša; Petrov, Ivana; Milenović, Miodrag (Frontiers in Medicine, 2018)
Postoperative analgesia is imperative in the youngest patients. Pain, especially if experienced during childhood, has numerous adverse effects - from psychological, through complications of the underlying disease (prolonged treatment, hospital stay and increased costs of the treatment) to an increase in the incidence of death due to the onset of the systemic inflammatory response. Peripheral blocks provide analgesia for 12-16h, and are safer due to rare side effects that are easier to treat . The continuous peripheral block (CPNB) has been increasingly used in recent years for complete and prolonged analgesia of pediatric patients, as well as a part of multidisciplinary treatment of complex regional pain syndrome. It has been shown that outpatient CPNB reduces the need for parenteral administration of opioid analgetics. It has also been proved that this technique can be used in pediatric patients in home conditions. Safety of CPNB is based on the increasing use of ultrasound as well as on the introduction of single enantiomers local anesthetics (ropivacaine and levobupivacaine) in lower concentrations. It is possible to discharge patient home with catheter, but it is necessary to provide adequate education for staff, patients and parents, as well as to have dedicated anesthesiology team. Postoperative period without major pain raises the morale of the child, parents and medical staff.